HUBUNGAN BAURAN PEMASARAN (MARKETING MIX) DENGAN OMSET APOTEK: TINJAUAN LITERATUR - Meridona; Sari, Seftika; Frimayanti, Neni (Journal Pharma Saintika, 2025)
Abstract: In recent years, the pharmaceutical and healthcare industries have undergone significant changes, marked by increasing competition among service providers, including pharmacies. Pharmacies must adapt their marketing plans in response to regulatory changes, service digitization, and increasing public health awareness. The purpose of this study is to conduct a systematic review of the existing literature on the relationship between pharmacy turnover success and marketing mix tactics. Databases including Google Scholar, PubMed, and Sciencedirect were searched, analyzing English and Indonesian-language publications published between 2015 and 2025 using the PRISMA method for systematic literature review. Of the 745 articles found, five were eligible for inclusion and further analysis. The results indicate that the key elements of the 7Ps of marketing—competitive pricing, product availability, and high-quality service involving both human resources and processes—have a significant impact on purchasing decisions and consumer loyalty. The study suggests that digital-based marketing initiatives and consumer education are important complementary elements in improving pharmacy performance. Overall, this study concludes that to maximize pharmacy turnover and competitiveness in the ever-changing healthcare environment, the 7P marketing mix must be implemented in an integrated and customer-oriented manner.